A corporalidade precarizada: o trabalho e as trabalhadoras terceirizadas nas universidades públicas brasileiras - Souza, Nathália Cardoso de (2022)
The present study has as object of investigation the issue of the pedagogy of the body at work expressed in the outsourced work of the cleaning servisse at public universities. Thus, we start from the following problematization: how outsourced cleaning work in a Public University forms/conforms/deforms the corporality of workers who survive in such working conditions? The objective is to identify and analyze which forms and content of body education determined by the conditions, relationships and processes of/in outsourced work and what they produce in the process of training the corporality of outsourced cleaning workers in public universities. The specific objectives are: a) understand and explain recent changes in the world of work, focusing on the forms of flexibility involved in the so-called outsourcing of work; b) to verify the implications of outsourcing work in the relationships and work processes of workers working in the outsourced cleaning service at the Public University; c) identify the content and forms of body pedagogy present in the forms of organization and cleaning work process management in public universities; d) explain the reflections of the nature of the cleaning work and its outsourcing on the corporality of workers. To this end, we carried out a Systematic Bibliographic Review choosing as a source of research the national scientific production available in digital libraries: 1) BDTD; 2) BTD Capes; 3) Google Scholar and for the analysis and interpretation of the data we took as analytical procedure the thematic content analysis according to Bardin (2011). The results of the survey pointed out that: I) the outsourcing of work is synonymous with the precarisation of work and the working class; II) that the predominant workforce of theoutsourced cleaning service within public universities is composed of the female workforce; III) outsourced cleaning service work imposes on male and female workers certain dynamics of body education and subjection of the corporality of the person subjected to such conditions of production and reproduction of life.